2021
DOI: 10.3389/fmed.2020.596405
|View full text |Cite
|
Sign up to set email alerts
|

Role of Palm Oil Vitamin E in Preventing Pre-eclampsia: A Secondary Analysis of a Randomized Clinical Trial Following ISSHP Reclassification

Abstract: Background: Preeclampsia is a significant cause of maternal and perinatal mortality worldwide. Oxidative stress plays a key role in its pathophysiology, hence antioxidants such as tocotrienol may be preventive against preeclampsia. In 2018, the ISSHP revised the definition of preeclampsia. In accordance with the new definition, we report a secondary data analysis from a clinical trial comparing palm oil vitamin E in the form of tocotrienol-rich fraction (TRF) against placebo, in preventing preeclampsia.Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The lack of effects of palm TRF on these subjects is expected because they were not hypertensive [ 91 ]. By contrast, Aminuddin et al demonstrated that palm TRF at 100 mg daily from 12–16 gestational weeks to delivery substantially reduced the risk of pregnancy-induced hypertension (odds ratio [OR]: 0.254; 95% confidence interval [CI]: 0.07–0.93) and pre-eclampsia (OR: 0.030, 95% CI: 0.001–0.65) amongst pregnant women [ 23 ]. However, the CI values for both effects were very large, which implies that the effect might not be consistent for all patients.…”
Section: Role Of Tocotrienol In Regulating Blood Pressurementioning
confidence: 99%
See 4 more Smart Citations
“…The lack of effects of palm TRF on these subjects is expected because they were not hypertensive [ 91 ]. By contrast, Aminuddin et al demonstrated that palm TRF at 100 mg daily from 12–16 gestational weeks to delivery substantially reduced the risk of pregnancy-induced hypertension (odds ratio [OR]: 0.254; 95% confidence interval [CI]: 0.07–0.93) and pre-eclampsia (OR: 0.030, 95% CI: 0.001–0.65) amongst pregnant women [ 23 ]. However, the CI values for both effects were very large, which implies that the effect might not be consistent for all patients.…”
Section: Role Of Tocotrienol In Regulating Blood Pressurementioning
confidence: 99%
“…Given this limitation, a direct translation of the effects of tocotrienol on blood pressure from existing animal models may be problematic because it is not tested in a pre-eclampsia model. Preliminary data from Aminuddin et al [ 23 ] suggested that tocotrienol could be used as a preventive agent rather than a reversal agent, based on animal studies. More comprehensive human clinical trials with larger sample size are required to prove the effects of TRF in preventing hypertension amongst women with pre-eclampsia.…”
Section: Role Of Tocotrienol In Regulating Blood Pressurementioning
confidence: 99%
See 3 more Smart Citations